Nasopharyngeal carcinoma in a 15-year-old: A rare pediatric tumor - Safina Zahir Msangi, MD; Mwajabu Saleh, MD; Jacob Mboka, MD; Akongnwi Jungong Cheo, MD; Frank J. Minja, MD; Sundeep M. Nayak, MD (Radiology Case Reports)
The unique challenges of diagnosing, treating, and managing pediatric nasopharyngeal carcinoma (NPC) in a lower-middle-income African country, Tanzania, are presented. Also, Computed Tomography (CT) imaging features that can distinguish NPC from other pediatric head and neck tumors are highlighted.